Modeling of charge transport in insulating dielectric for gas-insulated transmission line based on multiple trap levels - Zhang, Jia-Wei; Song, Chen (IEEE transactions on dielectrics and electrical insulation, 2018)
Space charge behavior in polymeric materials is of interest to the electrical engineering community and has significant effects on the behavior of the polymers that are used in gas-insulated transmission lines (GILs). For example, the space charge in certain insulating materials can cause severe distortion of the electric field that may even lead to breakdown of the materials. It is therefore important to understand the trapped charge distributions in these materials because they can be used as novel indicators for effective evaluation of the aging status and the electric withstand strength of these insulating materials. This paper addresses recent developments in the modeling of charge transport in polymers for use in GIL applications. A numerical model of bipolar charge transport in polymeric insulators is presented in this paper. This model was studied based on use of multiple trap levels and consideration of symmetrical parameters for the generation and transport of electrons and holes.
Gesehen am 31.03.2020